The Impact of Pre-Question Techniqueon Students’ Reading Comprehension Achievment at SMA N 1 Pegajahan - Sari, Bella Puspita; Nurhalimah, Puji Hariati, (Universitas Muhammadiyah Tapanuli Selatan, 2025)
The aim of this research was to investigate the impact of the pre-question technique on students' reading comprehension achievement at SMA N 1 Pegajahan. This research used a quasi-experimental design involving two classes: control class X-2 and experimental class X-4, each consisting of 36 students. The control class was taught using conventional methods, while the experimental class was given pre-question techniques during reading learning. The results showed that there were significant differences in post-test scores between the two groups. The average value of the control class is (77.22) while the standard deviation is (16.01). Meanwhile, the experimental class has an average value (95.57) with a standard deviation (7.71). The t-test analysis shows that the calculated t-value exceeds the t-table (6.6526) critical value for degrees of freedom (70) at the significance level (0.05) which confirms that the pre-question technique has a statistically significant positive effect on students' reading comprehension achievement.